The Development Tendency of 3D-Printed Bioceramic Scaffolds for Applications Ranging From Bone Tissue Regeneration to Bone Tumor Therapy - Fang, Zhixiang; Chen, Jihang; Pan, Jiangxia; Liu, Guoqiang; Zhao, Chen (Frontiers in Bioengineering and Biotechnology, 2021)
Three-dimensional (3D) printing concept has been successfully employed in regenerative medicine to achieve individualized therapy due to its benefit of a rapid, accurate, and predictable production process. Traditional biocomposites scaffolds (SCF) are primarily utilised for bone tissue engineering; nevertheless, over the last few years, there has already been a dramatic shift in the applications of bioceramic (BCR) SCF. As a direct consequence, this study focused on the structural, degeneration, permeation, and physiological activity of 3D-printed BCR (3DP-B) SCF with various conformations and work systems (macros, micros, and nanos ranges), as well as their impacts on the mechanical, degeneration, porosity, and physiological activities. In addition, 3DP-B SCF are highlighted in this study for potential uses applied from bone tissue engineering (BTE) to bone tumour treatment. The study focused on significant advances in practical 3DP-B SCF that can be utilised for tumour treatment as well as bone tissue regeneration (BTR). Given the difficulties in treating bone tumours, these operational BCR SCF offer a lot of promise in mending bone defects caused by surgery and killing any remaining tumour cells to accomplish bone tumour treatment. Furthermore, a quick assessment of future developments in this subject was presented. The study not only summarizes recent advances in BCR engineering, but it also proposes a new therapeutic strategy focused on the extension of conventional ceramics' multifunction to a particular diagnosis.